2013
DOI: 10.2527/jas.2012-6058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ractopamine administration and castration method on the response to preslaughter stress and carcass and meat quality in pigs of two Piétrain genotypes1

Abstract: The objective of this study was to evaluate the effects of ractopamine supplementation, castration method, and their interaction on the behavioral and physiological response to preslaughter stress and carcass and meat quality of 2 Piétrain genotypes. A total of 1,488 male pigs (115 ± 5 kg BW) were distributed according to a 2 × 2 × 2 factorial arrangement of treatments. The first factor was ractopamine supplementation with 2 groups of pigs (376 and 380 pigs each) receiving 7.5 mg/kg of ractopamine (RAC) or not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 49 publications
2
23
1
1
Order By: Relevance
“…Rocha et al (2013) reported RAC barrows required more physical contact to move during handling and transportation. Additionally, MarchantForde et al (2003) found pigs fed RAC took longer to voluntarily exit pens during weekly weight measurements, thus making them more difficult to handle.…”
Section: Performance Testmentioning
confidence: 99%
“…Rocha et al (2013) reported RAC barrows required more physical contact to move during handling and transportation. Additionally, MarchantForde et al (2003) found pigs fed RAC took longer to voluntarily exit pens during weekly weight measurements, thus making them more difficult to handle.…”
Section: Performance Testmentioning
confidence: 99%
“…Under stress, there is intense muscle glycogen degradation, producing high levels of lactic acid that are released into the bloodstream. As RAC is similar to natural catecholamine, it may cause physiological changes in animals, inducing stress (Rocha et al, 2013). However, in this study, the cortisol levels in the blood were not altered by either immunocastration or the addition of RAC, suggesting that these treatments did not induce stress in the animals.…”
Section: Stress Parametersmentioning
confidence: 42%
“…In a metaanalysis of results obtained in 23 studies from 1990 to 2006, it was concluded that, except for increased shear forces, dietary administration of ractopamine (5-20 ppm) has generally no deleterious effect on pork quality parameters such as color, firmness, water holding capacity, marbling score, and intramuscular fat content. Although the 7.5 ppm ractopamine dose improved carcass leanness, it also increased drip loss and toughness of pork (Rocha et al, 2013). It has been reported that even low doses (5 ppm) of ractopamine in the diet reduced tenderness slightly, as determined by both mechanical and taste panel evaluation, although there was no effect on other sensory properties such as flavor or juiciness (Patience et al, 2009).…”
Section: Effects On Meat Qualitymentioning
confidence: 93%